Dari Menanam Buah menjadi Menanam Rumah : TransformasiSosial Ekonomi Masyarakat Kota Batu - Al-fath, Edlin Dahniar (Journal of Indonesian Tourism and Policy Studies, 2016)
This research aims to describe the transformation of the village of Oro-oro Ombo from agriculture into modern tourism area. Oro-oro Ombo is one of the villages in Batu City which is undergoing rapid growth in tourism due to its accessibility to the various artificial parks. This study wants to understand the Oro-oro Ombo village after 2008, the year when the Batu Night Spectacular Began to be built on the communal land of Oro-oro Ombo. Previously, Oro-oro Ombo is an area of agriculture with the production of rice, corn, and fruits. At that time, Oro-oro Ombo is a quiet area with minimal highway lighting. However, since the construction of Batu Night Spectacular, this area changed drastically into a very crowded area. The crowd of Batu Night Spectacular encouraged the community of Oro-oro Ombo to construct tourism-based business, like lodge and food stall. In a period of 6 years, two hotels and 93 homestays have been established in the village. This amount does not include food stalls, shops trading business, and a restaurant. Most of the businesses owned by the community, to respond to the development of tourism, is built on agricultural land. In the end, the development of tourism changes people's livelihood from agriculture become tourism entrepreneurs. Even though start from a village scale, this study is expected to be a reflection of transformation all around Batu City from an agricultural town into a city of tourism. The study was conducted for six months in July until December 2015. The data collection methods for this research are observation, interview, and literature study.